PENGARUH KESADARAN WAJIB PAJAK, TINGKAT PENDAPATAN, PEMAHAMAN PERATURAN PERPAJAKAN DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Fatmawati, Adinda; Haryono (Publika Citra Media, 2024)
This study aims to examine the effect of taxpayer awareness, income level, understanding of tax regulations and tax sanctions on motor vehicle taxpayer compliance at Samsat Depok I. This type of research is quantitative. The data used in the study are primary data. The population in this study was 1,032,932 motor vehicle taxpayers. The sampling method used the slovin formula so that 100 respondents were obtained and the sampling technique used the simple random sampling technique. Data processing used the SPSS version 25 program. From this study, it was concluded that the variable of taxpayer awareness partially and significantly influenced motor vehicle taxpayer compliance, income level partially and significantly influenced motor vehicle taxpayer compliance, understanding of tax regulations partially and significantly influenced motor vehicle taxpayer compliance and tax sanctions partially and significantly influenced motor vehicle taxpayer compliance. Simultaneously has an influence on taxpayer awareness, income level, understanding of tax regulations and tax sanctions on motor vehicle taxpayer compliance at Samsat Depok I.